Effect of Copper Slag and Granite Powder on the Mechanical Properties of Reclaimed Asphalt Pavement Aggregate Concrete - T, Mahitha; J, Aswini (International Journal of Sustainable Construction Engineering and Technology, 2018)
The replacement of natural gravel aggregate with reclaimed asphalt as coarse aggregate would help in reduction of environmental and ecological effects. Researches were rarely performed by replacing fine aggregate in reclaimed asphalt pavement aggregate concrete. This project aims to investigate the feasibility of improving the strength of recycled asphalt aggregate concrete in which recycled asphalt aggregate is used as a partial replacement of coarse aggregate at 30%. Abrasion and attrition technique is used to modify or roughen the surface of RAP aggregates. Granite powder and copper slag are used as a partial replacement of sand at 5, 10, 15, 20 and 25% in Abrasion and attrition Treated Reclaimed Asphalt Pavement Aggregate Concrete (ABTRAPC). Thirty cubes, twenty cylinders and twenty beams of concrete with granite powder and thirty cubes, twenty cylinders and ten beams of concrete with copper slag were made and tested. The 7th and 28th day strengths were found out at these replacements. It was observed that the compressive strength, split tensile strength and flexural strength was found to be maximum at 15% replacement of sand by copper slag. The compressive strength was increased about 29.8% compared to ABTRAPC. Flexural strength similar to normal concrete and about 12.8% greater compared to ABTRAP concrete. The compressive strength and flexural strength was also increased to a maximum at 15% replacement of sand by granite powder and split tensile strength at 20% replacement of granite powder. The results showed that the potential of reclaimed asphalt aggregates as a partial replacement of coarse aggregates in concrete could be effectively enhanced with its a combination with granite powder or copper slag. The increase in compressive strength values and the increase in flexural strength values similar to normal concrete proved that this concrete has its potential to be used in pavement applications.